2023
DOI: 10.61650/alj.v1i1.17
|View full text |Cite
|
Sign up to set email alerts
|

ANDIN-MU: Development of Android-Based Descriptive Text Interactive Multimedia Materials in High School English Subjects

Mohammed Alameen Ahmed,
Nur Kumalasari

Abstract: In learning there is a process of changing the behavior of a person who is initially unaware of something then becomes aware. In other words, there is a process of conveying knowledge between teachers and students or using learning materials. The purpose of this study was to develop interactive multimedia based on Android descriptive text material for Class X SMA Pasuruan English. This study uses the ADDIE model. In this development model there are five steps in the process, but in this study the researchers m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…According to Muhammad, Marchy, et al, (2023), learning outcomes can be observed in the form of changes in student behavior that can be measured through changes in knowledge, attitudes, and skills. This change indicates an improvement and better development than before (Ahmed & Kumalasari, 2023;Darmayanti et al, 2023;Nasiha et al, 2023;Pradana & Uthman, 2023). There are several objectives of learning outcomes as stated by Irawan, (2022) providing information about students' progress in achieving learning goals through various activities;…”
Section: Introductionmentioning
confidence: 93%
“…According to Muhammad, Marchy, et al, (2023), learning outcomes can be observed in the form of changes in student behavior that can be measured through changes in knowledge, attitudes, and skills. This change indicates an improvement and better development than before (Ahmed & Kumalasari, 2023;Darmayanti et al, 2023;Nasiha et al, 2023;Pradana & Uthman, 2023). There are several objectives of learning outcomes as stated by Irawan, (2022) providing information about students' progress in achieving learning goals through various activities;…”
Section: Introductionmentioning
confidence: 93%
“…The auditor has several roles that he must play, which are: (Khoury, 2011;Ahmed & Kumalasari, 2023;Anisur Rahman, 2023a) 1. The role of supervision: The supervision of the internal audit activity in the public sector focuses on the departments and units of the public sector to ensure the extent of their compliance with the laws and regulations established to ensure the protection of state assets (Sungkawati et al, 2023).…”
Section: The Roles That the Internal Audit Should Playmentioning
confidence: 99%
“…A green audit aims to give citizens the information they need to question environmentally damaging companies from their customers and others and find ways to act wiser and more ecologically responsible, including renewable resources such as wind, solar, and energy. Geothermal (Verma et, 2012), on the other hand, the green audit aims to provide a complete understanding of the effects of global warming and the current and imminent effects of climate change and to provide a clear understanding of how the interrelationship between their health and the health of ecosystems, providing a comprehensive understanding of the principles and processes of development sustainable (Ogoc, 2015;Ahmed & Kumalasari, 2023). Put, green auditing aims to preserve the environment.…”
Section: Objectives Of the Green Auditmentioning
confidence: 99%